Morphological variability of bael varieties under rainfed conditions of hot semi-arid environment of western India (Indian Journal of Arid Horticulture, 2025)
Bael is an indigenous hardy fruit tree, its fruits are very rich source of riboflavin (Vitamin B,) with high nutraceutical and medicinal value. Every part of bael tree is used in one way or the other. During recent years, its importance has been highlighted in north India but, adequate attempts have not been made for its exploitation in Western India. A study keeping this fact in view was carried out to evaluate the bael genotypes for their growth behaviour and floral traits at Experimental Farm of Central Horticultural Experiment Station (CIAH), Vejalpur, Panchmahals, Gujarat during the years 2008 and 2010. Among the varieties evaluated for growth characters, plant height was recorded in CISH B-1, while plant spread, root stock and stem girth were recorded maximum in the variety NB-7. All the varieties exhibited significant difference with respect tofor most of the growth characters. Studies on floral biology revealed that the flower bud emergence started from 20" April and continued up to 23 June, while anthesis initiated from 12" May and completed by last week of June. Bud length and width varied from 10.00 to 13.00 mm and 7.00 to 9.50 mm while length and width of flower size ranged between 12.00 to 19.00 mm and 24.00 to 35.00 mm, respectively among the evaluated varieties. Number of petals in different varieties varied from 4 to 6 but majority of flowers showed only four petals. Stamen length varied from 7.00 mm (NB-7) to 9.00 mm (CISH B-2), whereas ovary length was recorded maximum in the genotype Pant Aparna (8.00 mm). Stigma length was recorded highest (3.50 mm) in the four varieties namely CISH B-2, Pant Aparna, NB-7 and NB-16, among the evaluated genotypes of bael. Pollen viability was observed more than 94 per cent in almost all the varieties.
Keywords: Bael; varieties; variability; morphology; flower